Prompts to increase stair climbing in stations: the effect of message complexity - Lewis, A; Eves, F (Human Kinetics, Inc., 2012)
Background/Objective: While point-of-choice prompts consistently increase stair climbing, experimental comparisons of message content are rare. Here, the effects of 2 messages differing in complexity about the health outcomes obtainable from stair climbing were compared. Methods: In a UK train station with 2 independent platforms exited by identical 39-step staircases and adjacent escalators, observers recorded travelers ascent method and gender from 8:00 A.M. to 10:00 A.M. on 2 weekdays during February/March 2008 (n = 48,697). Baseline observations (2-weeks) preceded a 3-week poster phase. Two posters (594 x 841mm) that differed in the complexity of the message were positioned at the point-of-choice between ascent methods, with 1 placed on each side of the station simultaneously. Logistic regression analysis was conducted in April 2010. Results: Omnibus analysis contained main effects of the intervention (OR = 1.07, CI = 1.02-1.13, P = .01) and pedestrian traffic volume (OR = 5.42, CI = 3.05-9.62, P < .001). Similar effects occurred for complex (OR = 1.10, CI = 1.02-1.18, P = .01) and simple messages (OR = 1.07, CI = 1.01-1.13, P = .02) when analyses controlled for the influence of pedestrian traffic volume. There was reduced efficacy for the complex message during busier periods (OR = 0.36, CI = 0.20-0.66, P = .001), whereas the simple message was immune to these effects of traffic volume. Conclusions: Pedestrian traffic flow in stations can influence message effectiveness. Simple messages appear more suitable for busy sites.